Fibroblast Growth Factor 23 (FGF‐23) Concentrations in Cats with Early Nonazotemic Chronic Kidney Disease (CKD) and in Healthy Geriatric Cats. (30th January 2013) - Finch, N.C.; Geddes, R.F.; Syme, H.M.; Elliott, J.
<x xml:space="preserve">Abstract</x> Background Fibroblast growth factor (FGF‐23) has an important role in phosphate regulation. Its clinical relevance in cats with CKD has not been explored previously. Hypothesis/Objectives The study objectives were (1) to determine whether FGF‐23 concentrations are increased in nonazotemic cats, cats which developed azotemia within 12 months of screening compared with cats that remained non‐azotemic, and (2) to evaluate the relationships between FGF‐23 and PTH and FGF‐23 and glomerular filtration rate (GFR). Animals Sixty‐two healthy client‐owned geriatric cats, 14 of which developed azotemia during the 12‐month follow‐up period. Methods Healthy nonazotemic cats were recruited prospectively into the study and followed for 12 months. At the study end‐point, cats were categorized into 3 groups according to plasma creatinine concentration. PTH, FGF‐23, and additional biochemical variables were evaluated at baseline and after 12 months. GFR was measured by a corrected slope‐intercept iohexol clearance method. Results FGF‐23 concentrations at baseline were found to be significantly increased in cats that developed azotemia (P = .001) compared with cats that did not develop azotemia. A significant positive relationship was identified between FGF‐23 and PTH, whereas the relationship between FGF‐23 and GFR was negative. Conclusions and Clinical Importance FGF‐23 concentrations predicted development of azotemia in geriatric cats. Positive relationships between FGF‐23 and PTH suggest an association between FGF‐23 and renal secondary hyperparathyroidism.